Business models for electronic open access journals and disciplinary differences : a proposal - Gumieiro, Katiúcia Araújo (2010)
Reports results of a research that aimed at studying the use of business models in the context of open access electronic scholarly journals publishing. Additionally, the work approaches disciplinary differences, particularly in terms of three issues, namely required publication speed, funding and features that involve the edition of a scholarly journal. In this context, the study aimed at proposing a model that allows identifying required elements to design business models appropriated to open access scholarly journals publishing. Along with identifying the elements, the study looked at the relationships between these elements and differences found between knowledge fields. Based on a bibliographic survey, the research adopted a qualitative approach that consisted of analysing the content of the literature reviewed. As a result, a business model for the activity of open access electronic journal publishing has been proposed. Based on Stähler’s approach, the model entails a set of four components, namely value proposition, products and/or services, value architeture and source of resources. Derived from this basic model, three other models are presented, each one representing particularities of the three major divisions of knowledge, Sciences, Social & Human Sciences and Arts & Humanities. As conclusion, features of business models for Sciences are considerably different from the other two divisions. On the other hand, there are important similarities between business models for the Social & Human Sciences and for Arts & Humanities.